Management - Emenike, Francis (My University, 2009)
It has been generally accepted that the only true competitive advantage for organizations over the long term is knowledge. This knowledge that can add value to an organization has become more complicated, and this requires combining and sharing knowledge and skills that several employees have. Despite a growing understanding of the importance of knowledge sharing, the sharing of information within organizations remains a challenge. Knowledge has been seen as a very difficult process to be share. Based on the importance of member to member transfer of knowledge, it has been realize that employee’s motivation is one of the barriers to knowledge sharing process initiatives The purpose of this study is to explore the effect of employee’s motivation and national culture in knowledge sharing within multinational companies with respect to a multinational company operating in Cameroon. Maslow hierarchy of need theory of motivation was use to illustrated people behavior in order to achieve their needs. This study uses single in-depth case study. Further, the findings are based on 7 semi structured interview questions and 10 employees were interviewed which provided the empirical basis for the case study. The result of the findings indicate that, extrinsic reward, fear of punishment, employees identification, career advancement, individualism/collectivism, language, trust and religion are factors that can help elucidate the myriad of reasons underlying employees’ willingness to engage in the sharing of knowledge within a multinational company despite the difficulties involve in sharing of knowledge
Keywords: Knowledge; Knowledge Sharing; Motivation; National Culture; MTN Cameroon; fi=Management|; fi=Master's Degree Programme in International Business|